Anthropomorphic phantom organ dose assessment using optically stimulated luminescence dosimeters unified in multi-detector computed tomography - Omar, R.S.; Hashim, S.; Bradley, D.A.; Karim, M.K.A.; N.D., Shariff (Elsevier, 2022)
This organ dose profile investigation is based on a technology that allows for the acquisition of densely sampled dose data, obtained using modified nanoDot™ OSLDs and a typical anthropomorphic Alderson Radiation Therapy phantom (ARTM 1092 model). The CT scan parameters were based on adult chest-abdomen and head region CT procedures, which were performed using a Siemens Somatom Definition AS+ at Hospital Sultanah Aminah in Johor. In studying the scanned region, the tube voltage and exposure duration values were considerably altered, with modulation approaches significantly altering the dosage distribution. In the head-neck procedure, the average absorbed dose per slice for the brain and thyroid was 3.469–33.645 mGy and 3.372–34.528 mGy, respectively. The distribution of chest-abdomen region organ dose mapping explains that the lungs received the highest organ dose, receiving a dose of 20.795 mGy from protocol P4, a setting of 140 kV tube voltage in the CT chest-abdomen protocol. The organ dosage levels in this investigation varied from 2.277 to 20.794 mGy, depending on tube voltage, tube current, and exposure period, as well as the organ composition, location, and surrounding anatomic structures. The average absorbed dosage in the lungs per slice varied from 3.439 to 20.794 mGy. The most significant coefficient of variation (CoV) for dosage samples of the lungs inside separate slices was 13%. The radiation dose patterns are consistent with similar tests and modalities, with variations dependent on tube voltage, exposure period, tube current, slice collimation, and pitch factor. The LED and CAL measured data (Mean ± SD) were determined to be an average of 4657 ± 563 and 1677 ± 31 counts, respectively. The supplied data is evidence of the microStar reader's superior performance.